2006
DOI: 10.1002/art.22180
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mechanism of action of turmeric supplements in the treatment of experimental arthritis

Abstract: Objective. Scientific evidence is lacking for the antiarthritic efficacy of turmeric dietary supplements that are being promoted for arthritis treatment. Therefore, we undertook studies to determine the antiarthritic efficacy and mechanism of action of a well-characterized turmeric extract using an animal model of rheumatoid arthritis (RA).Methods. The composition of commercial turmeric dietary supplements was determined by highperformance liquid chromatography. A curcuminoidcontaining turmeric extract similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 34 publications
9
150
0
Order By: Relevance
“…However very few studies (using gene therapy or any other treatment strategy) have demonstrated regression of established arthritis (16,17,43,44), and to date, total regression of established severe disease has not been achieved with any RA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However very few studies (using gene therapy or any other treatment strategy) have demonstrated regression of established arthritis (16,17,43,44), and to date, total regression of established severe disease has not been achieved with any RA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Funk et al (36) documented the effectiveness of an extract devoid of essential oils in preventing joint inflammation, while a hydroalcoholic extract of turmeric was demonstrated to inhibit joint inflammation and periarticular tissue destruction in a dose-dependent manner (37).…”
Section: Effect On Arthritismentioning
confidence: 99%
“…plant-based agents are being promoted for the management of arthritis. 4 Curcumin (CR), the yellow coloring agent found in turmeric (Curcuma longa, family Zingiberaceae), is a diferuloylmethane [1,7-Bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione] and has been used for centuries as a spice in the Indian subcontinent. 5 It has been reported to have a wide range of activities like anti-inflammatory, anti-oxidant, anti-parasitic, anti-mutagenic, anti-cancer, and anti-arthritic (both in vitro and in vivo), as suggested by many studies.…”
Section: Introductionmentioning
confidence: 99%